The Facts About Applying: Health Care Coverage and the Affordable Care Act - Meg McAlpine; Martie Gillen (EDIS)
President Obama signed the Affordable Care Act into law in March 2010, putting in place a set of reforms to health coverage in the United States. For Americans who have health insurance, they do not have to change their current plan under the health care law. However, those who do not have coverage will have the chance to shop for health insurance starting October 1 using the new Health Insurance Marketplace. This publication reviews some common questions about the new health care law and how it will affect citizens. This 3-page fact sheet was written by Meg McAlpine and Martie Gillen, and published by the UF Department of Family Youth and Community Sciences, October 2013. http://edis.ifas.ufl.edu/fy1394